NATURAL OPIUM AS ONE OF THE POSSIBILITIES FOR DRUG ABUSERS - Klusonova, Hana; Vlkova, Jana; Visnovsky, Peter (Biomedical papers, 2005)
Natural opium is a popular seasonal alternation for substance dependent people. Its processing, way of using, experience and change of habits was the aim of our study carried out via anonymous questionnaire and directed interview. 47 questionnaires were obtained. According to our results natural opium has been abused by people 19-42 years old, more than a half of them were male. Basic drug were pervitin in 57 %, marihuana in 33 %, a considerable part (30 %) was natural opium. Each grower produced approximately 35 g of raw opium in one season. The most frequent way of application was smoking, injecting and ``opium tea'' drinking. Almost a half of the clients (40 %) felt attenuation after application; relaxation, hallucination and central stimulation admitted 25 % of respondents. Health troubles had majority of the users. Combinations of natural opium with other drugs (alcohol, marihuana, pervitin) declared 45 % respondents, the effects of the combinations admitted one third of users. The examination for viral hepatitis confirmed more than a half of the clients; the major part of users from Olomouc, but only 25 % of users from Prostejov were tested for HIV. Opium consumption influenced habits of personal hygiene of more than a half of the users (57 %). Routine servicing of the spot of the needle insertion practiced a half of the responders. Majority of the abusers (79 %) obtained and closed out paraphernalia throw to the ``harm reduction'' program.
Keywords: Opium/Drug abuse/Anonymous questionnaire